PENERAPAN MODEL PEMBELAJARAN ARIAS UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN IKATAN KIMIA DI KELAS X MIA SMAN 12 PEKANBARU - Peggi Rivia Mahesa; Susilawati Susilawati; Johni Azmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to increase students learning achievement by implementation of ARIAS learning model on the chemical bonds subject in the class X MIA SMAN 12 Pekanbaru. The type of research is experimental research with randomized control group pretest-posttest design. The population consisted of 3 classes and the sample consisted of 2 classes randomly selected, namely the X MIA 5 class as the experimental class and the X MIA 6 class as the control class chosen randomly after homogeneity test. The experimental class is applied to the ARIAS learning model, while the control class does not apply the ARIAS learning model. Hypothesis testing uses the right-t-test, based on the results of data analysis obtained that t count> t table is 5.84> 1.67 meaning the implementation of ARIAS learning model can improve student learning achievement on the chemical bonds subject in the class X MIA SMAN 12 Pekanbaru with category increase in learning achievement high that is 0,83Key Words: ARIAS Learning Model, Learning Achievement, Chemical Bonds